VD_FINDINFO 127 vom 9. März 2022 - VD Tribunal cantonal (2022)
DÉCISION INCIDENTE, LITISPENDANCE, DROIT D'ÊTRE ENTENDU, DROIT INTERNATIONAL PRIVÉ | 29 al. 2 Cst., 9 LDIP, 237 CPC (CH), 59 al. 2 let. d CPC (CH), 62 CPC (CH)